KOMITMEN ANGGARAN PENDIDIKAN Dl KOTA PENDIDIKAN YOGYAKARTA MASIH BELUM MENCAPAI 20 PERSEN - Triyastuti Setianingrum (Populasi, 2007)
It is always interesting to observe the face of education in Indonesia. One interesting factor is related to bugdeting on education in Indonesia has not reach 20% of the national budget. It is in connection to the political will of the local government to improve the educational level in Yogyakarta. Many obstacles have to be faced by the government to pursuit this 20%. At the end this will remain as a homework to the governemnt to reach the target budgeting of 20% for education. The goals to provide a cheap, but high quality education should be achieved to increase the quality of our children in the future.